2003
DOI: 10.1179/108331903225002434
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Therapeutic Exercise in the Conflicting and Unstable Shoulder

Abstract: Context: The use of therapeutic exercise and manual therapy in rehabilitation of the unstable and conflicting shoulder (UCS) is widespread. In the literature, there are several electromyographical studies that have analysed the effect of specific physical exercises and clinical trials on the effectiveness of specific rehabilitative protocols. However, it has not been established yet what is the best intervention for these disorders. Objective: In order to establish general recommendations for the treatment of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…This finding points to the positive effect of exercise, which is known to be a basic therapeutic modality in shoulder pain relief and joint range of motion improvement when used alone or combined with specific physiotherapy programs. 43 The results of the comparison of the two groups in our study showed significantly better improvement only for passive extension range and palpation sensitivity for the laser group. While better passive extension range may be a result of the laser effect, it may also be due to our patient selection criteria, according to which patients with restriction of active and passive joint range of motion were also included in the study, regardless of the specific diagnosis for the shoulder pain.…”
Section: Discussionmentioning
confidence: 44%
“…This finding points to the positive effect of exercise, which is known to be a basic therapeutic modality in shoulder pain relief and joint range of motion improvement when used alone or combined with specific physiotherapy programs. 43 The results of the comparison of the two groups in our study showed significantly better improvement only for passive extension range and palpation sensitivity for the laser group. While better passive extension range may be a result of the laser effect, it may also be due to our patient selection criteria, according to which patients with restriction of active and passive joint range of motion were also included in the study, regardless of the specific diagnosis for the shoulder pain.…”
Section: Discussionmentioning
confidence: 44%
“…In addition, studies often focus on interventions for 1 or 2 subcategories of shoulder diagnosis, some with only a limited number of dependent variables. 3,6,7,8,22,29 This may limit the application of the study. Several studies have noted the recalcitrant nature of shoulder dysfunction.…”
mentioning
confidence: 99%